On Baguio's Past - Scheerer, Otto (The Archive; No 1 (1931): Accessory Paper No. 1: On Baguio's Past, 2024)
Excerpt Having been a resident of Báguio in pre-American days, I am often asked to speak about former conditions in this now far-famed mountain-resort of the Philippines. The following pages are intended to convey information of the desired kind up to the end of the Spanish regime. Báguio and the country around it are the home of a group of Igórots [literally ‘mountaineers] called Ibáloys, on whose ethnography we have valuable papers from Worcester, Barrows, and others. To obtain knowledge especially of the life of the Ibáloys inhabiting Báguio and its outlying settlements in the past, two means are at our disposal. We may ransack the records Spanish authors have left us of former happenings in that area, or we may, by questioning the older tribesmen themselves, try to bring out what local traditions have survived the rush of modern times. I have drawn from both sources and, much as they leave to be desired, there is no reason for withholding from wider knowledge information the very insufficiency of which might incite the academic or patriotic interest of others to bring to light further material. In fact, unimportant as may appear today the part of which Igórot records play in Philippine historical research, interest in them will increase as the mountain peoples of northern Luzon, gaining in numbers and culture, come to establish themselves more fully in the comity of their brothers of the lowlands and thus help to consolidate the Philippine nation. In accordance with the foregoing this paper is divided into a review of certain Spanish chronicles and an account of original research of the writer.